Nineteen new combinations and a new name in Breynia J.R. Forst. & G. Forst. (Phyllanthaceae) from Indian subcontinent - Chakrabarty, T.; Balakrishnan, N. P. (Bangladesh Journal of Plant Taxonomy, 2012)
Nineteen new combinations and one new name are proposed in Breynia for taxa previously treated in Sauropus. DOI: http://dx.doi.org/10.3329/bjpt.v19i2.13125 Bangladesh J. Plant Taxon. 19(2): 119-122, 2012 (December)